THE ANNAUL RAINFALL VARIATION OF THE SABARMATI BASIN USING NON PARAMATRIC MANN-KENDALL TEST (International Journal of Food and Nutritional Sciences, 2022)
The rainfall studies in India is whether the monsoon rainfall has changed over the last few decades and whether a change is probably to occur in future. Nonetheless, it is difficult to identify the probable future trend of rainfall, it is possible to detect the nature of changes that have occurred in the past. The Non-parame trie Mann- Kendall test has been used to evaluate the long-term changes/trends in the annual rainfall records of the Sabarmati Basin. The data analyzed for present work consists of long-term annual rainfall series entailable for 4 rain gauge stations located in the basin. The Mann-Kendall's Tau (z) for the Sabarmati Basin is 0.067. The positive value suggests that the rainfall trend for the given period is increasing. However, although the value is positive, the application of this non- parametric test to the annual rainfall data of the basin designates no significant trend at 0.01 and 0.05 level.